INFORMATION - COMMUNICATION TECHNOLOGIES IN TEACHING TECHNICAL WORKS - SEBENOVA, Iveta (Trends in education, 2013)
Nowadays the role of information-communication technologies is very important. ICT is an inevitable component of education processes even in primary education. Paper describes possibilities of information-communication technologies implementation in teaching technical works. Author discusses the advantages and disadvantages of using informationcommunication technologies during the technical works classes.
Keywords: information-communication technologies; technical works teaching primary school education